Riqueza e estrutura de comunidades de formigas (Hymenoptera: Formicidae) associadas a flores em fragmentos de caatinga na região de Milagres, Bahia - Brito, Alessandra Fonseca (2011)
Aiming to determine if the seasonal dynamics of the vegetation, among the dry and wet seasons, affects the richness and community composition of ants associated to flowers, two areas of Caatinga in Milagres, Bahia, were surveyed. Thirty four species of ants associated to 42 species of plants, were found, and among the two periods, the riches of species of ants remained the same (23 species), varying in the composition, that presented a similarity of only 35%. With relation the plants, were found 42 flowery vegetable species, presenting a similarity of only 31% among the periods. The two areas of caatinga present a different structural complexity, for they possess different vegetable compositions, and in that way, the cluster analyses, for the index of Jaccard, it shows that the effect of the vegetation type (space factor) it was shown more important as a structural factor on the community of ants than the seasonal effect (temporary factor), caused by the climatic variations that happen of the transition of the dry period for the wet. Through the analysis of Multiple Regression, it was proven that the riches of species and absolute frequency of ants in flowers, it was not influenced by the riches of species of flowery plants. The species Camponotus blandus, more frequent in the areas, it is considered typical of open environments and of degraded areas, being common in caatinga areas. However, was a larger frequency of that species during the wet period, when the structural complexity is larger, with intense bloomed of plants, and larger vegetable covering.